2020
DOI: 10.1021/acs.jpcc.0c01296
|View full text |Cite
|
Sign up to set email alerts
|

Combined DRIFTS and DFT Study of CO Adsorption and Segregation Modes in Pt–Sn Nanoalloys

Abstract: This contribution aims at rationalizing the observations made by in situ IR spectroscopy during CO adsorption over 1.8 nm Pt-Sn nanoparticles by Density Functional Theory (DFT) calculations and describing the environment and electronic properties of surface Pt atoms modified by Sn. Pt surface enrichment upon CO exposure was observed by DRIFTS (diffuse reflectance FT-IR spectroscopy) and rationalized by the theoretical calculations, which also indicated that isolated Pt was favored over Pt pairing in a Sn-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…After CO adsorption at room temperature, the maximum of the CO absorption band for Pt 3 Sn/CeO 2 is close to 2037 cm −1 (Figure 4e), which is similar to reported values for CO adsorption on the tin-rich platinum alloy 40,42 and significantly different from the corresponding maxima at 2062 cm −1 for Pt/ Ce 0.5 Sn 0.5 O 2 (Figure 4c) and at 2080 cm −1 for Pt/CeO 2 (Figure 4d). During the subsequent dosing of oxygen, the behavior of the materials is also different.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…After CO adsorption at room temperature, the maximum of the CO absorption band for Pt 3 Sn/CeO 2 is close to 2037 cm −1 (Figure 4e), which is similar to reported values for CO adsorption on the tin-rich platinum alloy 40,42 and significantly different from the corresponding maxima at 2062 cm −1 for Pt/ Ce 0.5 Sn 0.5 O 2 (Figure 4c) and at 2080 cm −1 for Pt/CeO 2 (Figure 4d). During the subsequent dosing of oxygen, the behavior of the materials is also different.…”
Section: Resultssupporting
confidence: 91%
“…Due to the difference in the positions of the linear CO absorption band on platinum for Pt/CeO 2 and Pt/Ce 0.5 Sn 0.5 O 2 catalysts, we considered a possibility of Pt/Sn alloy formation for the pre-reduced Pt/Ce 0.5 Sn 0.5 O 2 catalyst . Therefore, we decided to compare the platinum state in the Pt/Ce 0.5 Sn 0.5 O 2 catalyst to that in the specially prepared reference material containing Pt 3 Sn nanoparticles on ceria (Pt 3 Sn/CeO 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it disappeared in the case of PtSnCe/SiO 2 , accompanying a decreased intensity of the linear adsorption peak at 2060 cm −1 . The disappeared bridge-bonded CO over PtSnCe/SiO 2 suggests that the SnO 2 breaks the ensemble of Pt atoms and forms a checkerboard Pt-Sn surface structure [ 24 , 50 ] because CO does not adsorb at the bridge sites between Sn and Pt. The decreased intensity of the peak at 2060 cm −1 , in comparison with PtCe/SiO 2 , can be explained as the reduced surface coverage of CO due to the presence of SnO 2 [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…On Pt 1 Sn 1 /SiO 2 , the bridgebonded CO was not present, and the linearly bonded peak had much lower intensity. Because CO does not adsorb at the bridge sites between Sn and Pt, the data suggest that Sn broke the ensembles of Pt atoms on the NP surfaces and created a checkerboard Pt-Sn surface structure (58). The decreased intensity of the linearly bonded CO adsorption peak was consistent with reduced surface coverage of CO on the PtSn compared with Pt ( 59 To further confirm the presence of PtSn surface alloys, XPS of the freshly reduced Pt 1 Sn 1 /SiO 2 catalyst showed that the atomic ratio of Pt and Sn was ~1, consistent with the nominal loading (fig.…”
mentioning
confidence: 98%